Perancangan Tekstil Dengan Sumber Ide Griffin Untuk Fesyen Komunitas Solo Kick’s Up - Bagus Firman Pradana; Nanang Rizali (Texture:Art and Culture Journal, 2022)
This design developed Griffin as a basis for making textiles and functioned in the sneakerhead community fashion  named  Solo  Kick’s  Up,  this  activity  was  an  introduction  to  a  nature  and  identity,  depicting  the digital  world  while  offering  unique  and  interesting  visuals.  The  purpose  of  this  design  is  to  develop  an illustration design motif with popular visual art processing with consideration of the fashion function for the Solo Kick’s Up community. The method used consists of; design methods, design concepts and visualizations. The design method goes through the stages of problem analysis, problem solving strategies, data collection, testing, and determining the initial design ideas. The design concept includes the rationale for designing textiles. Visualization is the stage of visualizing the concept of a design plan.The  results  of  this  textile  design  are  as  follows:  (1)  Greek  mythological  creature  Griffin  as  a  source  of textile design ideas in order to increase the value of textiles, The results of the design succeeded in making 7 textile designs. (2) The application of Griffin textile design as a community fashion produces outer fashion products that are memorable, attractive, unique and different from the others.